Plagiarism: The Weakest Link in Teaching Research Skills - Youcef, BEGHOUL (Sciences humaines, 2014)
تتناول هذه المقالة ظاهرة استفحلت وأخذت بعدا عالميا وهي ظاهرة السرقة العلمية في عصر رقمي أصبحت فيه المعلومات والمعطيات العلمية افتراضية أكثر من ذي قبل وفي متناول الجميع. باستعمال استبيان وزِّع على عينة من الطلبة وعينة من الأساتذة يحلل هذا البحث هذه الظاهرة في سياق مذكرة يقدمها طلبة ل م د لنيل شهادة  الماستر في اللغات التطبيقية في قسم الآداب واللغة الإنجليزية، جامعة قسنطينة 1. ويفترَض في هذا البحث أن كثيرا من الطلبة لا يدركون تماما ما تعنيه السرقة العلمية حقا لأن هذا المفهوم لا يدرَّس إلا نادرا في مقياس تدريس مناهج ومهارات البحث.  هذا بالإضافة إلى أن الطلبة يقدمون أبحاثهم في وقت قصير ويشرف عليهم عدد قليل من الأساتذة. كل هذا وذاك عقد مشكل السرقة العلمية فأصبحت صعبة التشخيص ولا مفر منها عند كثير من الطلبة. وتوحي أجوبة الأساتذة والطلبة على السواء أيما إيحاء على ما هو مفهوم السرقة العلمية في واقعهم اليومي وما يترتب عليه من نتائج وخيمة على المدى القريب والمدى البعيد وكيفية كشف هذه السرقة من قبل المشرفين أثناء إشرافهم على أبحاث متعددة وفي أجل قصير وكذا كيفية اجتناب الطلبة لهذه السرقة من أجل سلوك أخلاقي والتزام بقوانين الملكية العلمية وهي أمور من شأنها ترقية الفكر الإبداعي والأصيل             This paper examines plagiarism which is a widespread phenomenon that has gained a universal dimension in a digital age where knowledge and data are growing more virtual and more accessible than ever.  Using a questionnaire administered to a sample of students and a sample of teachers, the author tries to analyse this phenomenon in the context of the research projects undertaken by LMD students in partial fulfilment for the requirements of a Master’s in applied languages at the Department of Arts and English Language, University 1 of Constantine. The hypothesis is that many students are not aware of what plagiarism really includes as they are seldom taught this appropriately in the module of research methods and skills. Furthermore, the great number of students, the short time for submissionand lack of supervisors have made the problem even more complex, far out of control and practically unavoidable. The responses of both teachers and students are quite insightful in matter of what plagiarism fully implies, what its consequences are in the short and long run, how to detect it by supervisors in short term mass research projects and how to avoid it by students in order to behave ethically, abide by the laws governing intellectual property and, by the same token, promote original and creative thought. Key Words: Digital, intellectual property, original thought, plagiarism, unethical